Suppression of Flaming Combustion and Thermal Decomposition of Condensed Matter at Different Heights of the Beginning of Water Array Motion; Combustion, Explosion, and Shock Waves; Vol. 56, iss. 1 - Volkov R. S. Roman Sergeevich (2020, 2020)
Title screen